Immobilisasi Ion Logam Berat Ni2+ dan Cr3+ pada Geopolimer Berbasis Abu Layang dan Serat Daun Nanas - Ratri, Irwandari Rahma Nur; Kusumastuti, Ella; Mahatmanti, F Widhi (Universitas Negeri Semarang, 2018)
Geopolimer was material which has function as successor of OPC, but it has brittle and have to add some fiber to make it strong. The purpose of this research was to find of the number of pineapple fiber optimum (b/b) which is on synthesis geopolimer, and immobilizes ion metal in weight Ni2+ and Cr3+ in the pineapple fiber optimum. This research was doing with two steps, the first is the background of the pineapple leaves fiber optimum and immobilizes ion metal in weight Ni2+ and Cr3+ in the pineapple fiber optimum. The result show that pineapple fiber get 0,5% (b/b) with strong of pressure was 54,82 MPa and the strong of pull was 1,70 MPa, then after put metal ion Ni2+ and Cr3+ it getting decrease of strong pressure 40,65 MPa and 39,17 MPa, then for the the strong of pull was kuat tarik 1,62 MPa and 1,46 MPa. Reserve ribbon in 2970,80 cm-1; 2971,23 cm-1 dan 2971,45 cm-1 showed the bunch C-H cellulose fiber that is on the geopolimer with put of the fiber. An analyzes of morphology SEM was showed that has a particle of fiber in the matrix geopolimer, the dust kite was not has reaction, and has a pore.